Novel Oligopyrrole Carboxamide based Nickel(II) and Palladium(II) Salens, Their Targeting of Human G‐Quadruplex DNA, and Selective Cancer Cell Toxicity. Issue 18 (8th September 2016) - Ali, Asfa; Kamra, Mohini; Roy, Soma; Muniyappa, K.; Bhattacharya, Santanu
Abstract: DNA targeting by various metal complexes is a key strategy toward the restriction of cancer cell proliferation. Toward this end, we designed and synthesized novel salen‐based Ni II and Pd II metal complexes with positively charged flanking side chains comprising N ‐methylpyrrole carboxamides of varying lengths. The compounds showed high specificity toward G‐quadruplex DNA over duplex DNA. Sufficient inhibition of the telomerase activity was observed, which was ascertained by the prominent restriction of cancer cell proliferation in the long‐term cell viability and telomerase inhibition assays. The compounds exhibited selective cancer cell death following an apoptotic pathway. Analysis of the binding mode showed partial stacking of the salen moiety over the G‐tetrads and association of the pendant oligopyrrole carboxamide units with the grooves. The conjugation of the tetrad‐binding metal salen core with groove‐oriented flexible oligopyrrole moieties resulted in the high selectivity and stabilization of the human G‐quadruplex DNA structures. Abstract : A toxic brew : New salen‐based Ni II and Pd II complexes with flanking N ‐methylpyrrole carboxamide side chains of varying lengths are synthesized. The complexes show high stabilization of G‐quadruplex DNA and efficient telomerase inhibition, which results in selective toxicity toward cancer cells over normal cells by following an apoptotic pathway.